2019
DOI: 10.1371/journal.pone.0210079
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting aneuploidy profile of surgically retrieved spermatozoa by whole exome sequencing molecular karyotype

Abstract: Previous studies, including our own, have reported that spermatozoa isolated from the testis have remarkably higher occurrence of aneuploidy once isolated from azoospermic men. This notion, however, did not translate into a lower pregnancy rate nor a greater proportion of miscarriages. Indeed, ICSI offspring generated from surgically retrieved gametes did not suffer from increased karyotypic aneuploidy than children generated from ejaculated specimens. In recent years, aneuploidy assessments on a larger number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…However, surgical sperm retrieval [254] carries risk of anesthetic and surgical complications. Furthermore, possible higher aneuploidy rate in testicular sperm is a concern [255] despite a recent report of opposing view [256]. Therefore, the use of testicular sperm in clinical management of nonazoospermic patients with high SDF is still debated.…”
Section: Use Of Testicular Sperm For Intracytoplasmic Sperm Injectionmentioning
confidence: 99%
“…However, surgical sperm retrieval [254] carries risk of anesthetic and surgical complications. Furthermore, possible higher aneuploidy rate in testicular sperm is a concern [255] despite a recent report of opposing view [256]. Therefore, the use of testicular sperm in clinical management of nonazoospermic patients with high SDF is still debated.…”
Section: Use Of Testicular Sperm For Intracytoplasmic Sperm Injectionmentioning
confidence: 99%
“…This has been corroborated by others 42 and recently demonstrated by a study using whole-exome sequencing. 43 It is common practice to transfer embryos at the blastocyst stage to promote embryonic self-selection, higher live birth rates, and reduced multiple gestation. 44 However, there has been some concern that extended in vitro culture can cause embryo gene expression alterations, leading to large offspring syndrome.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Because sperm DFI is also lower in testicular spermatozoa than in the ejaculate, higher aneuploidy in the ejaculated specimen may therefore be caused by an epididymal phagocytotic defect that fails to sequester abnormal gametes in the cauda, causing them to be leaked during ejaculation. 43 In these cases, a ubiquitin-based sperm assay, as reported in the mouse, may be a suitable intervention to identify and destroy abnormal spermatozoa within the epididymal epithelium. 48…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, new data generated by whole-exome sequencing molecular karyotype suggest that sperm aneuploidy in testicular specimens is not a major concern 71 . In this series, paired assessments in ejaculated and surgically retrieved testicular samples of non-azoospermic patients with elevated SDF in semen showed that the rates of aneuploidy (1.3% versus 8.4%, respectively, P = 0.02) were lower in testicular sperm than in ejaculated sperm.…”
Section: Offspring Healthmentioning
confidence: 99%